Rocket to the Moon! - Graphic Novel - Brown, Don 1949- (New York : Amulet Books, 2019)
"On July 20, 1969, Neil Armstrong took "one small step for man, one giant leap for mankind" when the Apollo 11 landed on the moon. But it wasn't just one man who got us to the moon. Rocket to the Moon! explores the people and technology that made the moon landing possible. Instead of examining one person's life, it focuses on the moon landing itself, showing the events leading up to it and how it changed the world. The book takes readers through the history of rocket building: from ancient Chinese rockets, to "bombs bursting in air" during the War of 1812, to Russia's Sputnik program, to the moon landing."--
Includes bibliographical references (pages 126-128) and index.
Keywords: Project Apollo (U.S.) -- Comic books, strips, etc; Project Apollo (U.S.) -- Cartoons and comics; Space flight to the moon -- Comic books, strips, etc; Space flight to the moon -- Cartoons and comics; Cartoons and comics; Moon -- Comic books, strips, etc; Moon -- Cartoons and comics; Comics (Graphic works)